PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA MATERI SISTEM TATA SURYA KELAS VI SEKOLAH DASAR - Davina Vina; Filia Prima Artharina; Diana Endah Handayani (STKIP Subang, 2025)
This research is motivated by the lack of interactive visual media, which makes it difficult for students to understand abstract concepts, particularly the solar system material. Innovative learning media are needed to help students comprehend the material more effectively. The purpose of this study is to determine the results, feasibility, and practicality of the Solar System Pop-Up Book learning media for sixth-grade students at SD Negeri 1 Blimbing. This research uses the Research and Development (R&D) method with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 19 sixth-grade students and one sixth-grade teacher at SD Negeri 1 Blimbing. The resulting product is a pop-up book learning media featuring interactive three-dimensional illustrations, equipped with QR codes containing augmented reality (AR), Wordwall interactive quizzes, and links to current news. The media expert validation results obtained a percentage of 93.33%, while the material expert validation results reached 87.5%, with an average of 90.41%, categorized as